Private and Shared Taste in Art and Face Appreciation - Leder, Helmut; Goller, Juergen; Rigotti, Tanya; Forster, Michael (Frontiers in Human Neuroscience, 2016)
Whether beauty is in the eye of the beholder or shared among individuals is a longstanding question in empirical aesthetics. By decomposing the variance structure of data for facial attractiveness, it has been previously shown that beauty evaluations comprise a similar amount of private and shared taste (Hönekopp, 2006). Employing the same methods, we found that, for abstract artworks, components that vary between individuals and relate to personal taste are particularly strong. Moreover, we instructed half of our participants to disregard their own taste and judge stimuli according to the taste of others instead. Ninety-five women rated 100 abstract artworks for liking and 100 faces for attractiveness. We found that the private taste proportion was much higher in abstract artworks, accounting for 75% of taste compared to 40% in the face condition. Abstract artworks were also less affected than faces by the instruction to rate according to others’ taste and therefore less susceptible to incorporation of external beauty standards. Together, our findings support the notion that art—and especially abstract art—crystallizes private taste.